(untitled) (Journal of Pakistan Orthopaedic Association, 2024)
The healthcare landscape in Pakistan is as complex as its rich cultural tapestry. For pediatric orthopedic conditions, cultural beliefs and practices significantly influence medical decisions. This editorial emphasizes the urgent need for culturally sensitive approaches in healthcare to ensure effective and timely medical care for children. Traditional and Alternative Medicine In Pakistan, traditional and alternative medicine is deeply ingrained in the cultural fabric. According to Abbasi et al.1, an overwhelming 80% of parents turn to traditional remedies before seeking modern medical treatments for their children’s orthopedic conditions. This reliance often leads to delays in receiving appropriate care, resulting in worsened conditions that could have been managed more effectively if treated earlier. Healthcare providers must recognize and respect the value placed on traditional medicine. Instead of dismissing these practices, medical professionals should aim to integrate traditional remedies within the modern healthcare framework. Collaborative efforts could involve training traditional healers in basic modern medical knowledge and encouraging them to refer cases that require advanced medical intervention. Public health campaigns need to focus on educating the populace about the benefits of integrating both approaches, thereby ensuring timely medical intervention without undermining cultural beliefs2.